Efficacy of dehydroepiandrosterone (DHEA) to overcome the effect of ovarian ageing (DITTO): a proof of principle double blinded randomized placebo controlled trial - Narkwichean, Amarin; Maalouf, Walid E.; Baumgarten, Miriam; Polanski, Lukasz; Raine-Fenning, Nick; Campbell, Bruce K.; Jayaprakasan, Kannamannadiar (Elsevier, 2017)
Objective: To evaluate the effect of DHEA supplementation on In-Vitro Fertilisation (IVF) outcome as assessed by ovarian response, oocyte developmental competence and live birth rates in women predicted to have poor ovarian reserve (OR). The feasibility of conducting a large trial is also assessed by evaluating the recruitment rates and compliance of the recruited participants with DHEA/placebo intake and follow-up rates. Study design: A single centre, double blinded, placebo controlled, randomized trial was performed over two years with 60 women undergoing in-vitro fertilisation (IVF). Subjects were randomized, based on a computer-generated pseudo-random code to receive either DHEA or placebo with both capsules having similar colour, size and appearance. 60 women with poor OR based on antral follicle count or anti-Mullerian hormone thresholds undergoing IVF were recruited. They were randomised to receive DHEA 75 mg/day or placebo for at-least 12 weeks before starting ovarian stimulation. They had long protocol using hMG 300 IU/day. Data analysed by “intention to treat”. Ovarian response, live birth rates and molecular markers of oocyte quality were compared between the study and control groups. Results: The recruitment rate was 39% (60/154). A total of 52 participants (27 versus 25 in the study and placebo groups) were included in the final analysis after excluding eight. While the mean (standard deviation) DHEA levels were similar at recruitment (9.4 (5) versus 7.5 (2.4) ng/ml; P = 0.1), the DHEA levels at pre-stimulation were higher in the study group than in the controls (16.3 (5.8) versus 11.1 (4.5) ng/ml; P < 0.01). The number (median, range) of oocytes retrieved (4, 0–18 versus 4, 0–15 respectively; P = 0.54) and live birth rates (7/27, 26% versus 8/25, 32% respectively; RR (95% CI): 0.74 (0.22-2.48) and mRNA expression of developmental biomarkers in granulosa and cumulus cells were similar between the groups. Conclusion: Pre-treatment DHEA supplementation, albeit statistical power in this study is low, did not improve the response to controlled ovarian hyperstimulation or oocyte quality or live birth rates during IVF treatment with long protocol in women predicted to have poor OR.